Each Aeon Free After The First One: The Welsh Underground, special edition of Angel Exhaust, 21, eds. Andrew Duncan and John Goodby - John Goodby (Angel Exhaust, 2010)
Groundbreaking anthology (16 poets represented: John James, Peter Fincvh, John Powell Ward, Philip Jenkins, Paul EvansIain Sinclair, David Barnett, Ralph Hawkins, Chris Ozzard, David Greenslade, Graham Hartill, N. S. Macias, Zoe Skoulding, Niall Quinn, John Goodby, Rhys Trimble) and critical essays on Welsh avant-garde and alternative poetry by: Nerys Williams (Finch), Nigel Jenkins (Childe Roland), Andrew Duncan (Euros Bowen; Lynette Roberts), John Goodby (general), Alun Llwyd, Eurig Salisbury, Graham Hartill (interview), Chris Ozzard (memoir), on both anglophone and cymreig avant-gardes. This is the first attempt to establish the validity and worth of alternative poetry and a tradition of it in, or identifying with, Wales.